Penerapan Arsitektur Bioklimatik Pada Resort Kawasan Pesisir Pantai Di Jawa Timur - Cesaridha, Ghefira Pramesthi; Winarto, Erwin Djuni (Universitas Medan Area, 2025)
The development of lodging places that pay less attention to natural factors can reduce environmental quality due to excessive energy use which results in depletion of natural resources, as well as waste of energy. The concept of Bioclimatic Architecture is a design method that combines the principles of the natural environment with human needs. The main focus is to create a comfortable environment while minimizing energy consumption. Bioclimatic design concepts are considered, including natural ventilation and lighting, solar shading, passive cooling techniques, etc. The overall idea developed in the bioclimatic design concept incorporates natural strategies, intelligent design, sustainable elements, regenerative design principles, and effective and efficient use of energy to reduce negative impacts on the environment. This research uses a quantitative comparative method using document analysis data as well as comparing in-depth aspects related to resorts in East Java located in coastal areas. This study aims to determine and compare the application of bioclimatic architecture in resorts in coastal areas located in East Java.